2014
DOI: 10.1097/prs.0000000000000471
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleic Acid Scavenger Polyamidoamine Third-Generation Dendrimer Inhibits Fibroblast Activation and Granulation Tissue Contraction

Abstract: Background Pathologic cutaneous scarring affects over 40 million people worldwide and costs billions of dollars annually. Understanding mechanisms of fibroblast activation and granulation tissue contraction is the first step toward preventing pathologic scarring. The authors hypothesize that nucleic acids increase fibroblast activation and cause granulation tissue contraction and sequestration of nucleic acids by application of a nucleic acid scavenger dendrimer, polyamidoamine third-generation dendrimer, will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…These CpG stimulated cells both stably expressed α-Sma and PDGFRα, a key receptor for fibrosis generation and an increased resistance to apoptosis and reduced caspase-3 levels, possibly mediated through HIF-1α expression [65]. In mouse fibroblast it was also shown that CpG stimulation leads to enhanced myofibroblasts and cytokine induction and using a wound healing model in mice it was shown that blocking the nucleic acid with a third-generation dendrimer reduced granulation tissue [66]. TLR9 gene deleted mice are protected from experimental liver fibrosis also suggesting a universal phenomenon [67].…”
Section: Internal Tlrsmentioning
confidence: 99%
See 1 more Smart Citation
“…These CpG stimulated cells both stably expressed α-Sma and PDGFRα, a key receptor for fibrosis generation and an increased resistance to apoptosis and reduced caspase-3 levels, possibly mediated through HIF-1α expression [65]. In mouse fibroblast it was also shown that CpG stimulation leads to enhanced myofibroblasts and cytokine induction and using a wound healing model in mice it was shown that blocking the nucleic acid with a third-generation dendrimer reduced granulation tissue [66]. TLR9 gene deleted mice are protected from experimental liver fibrosis also suggesting a universal phenomenon [67].…”
Section: Internal Tlrsmentioning
confidence: 99%
“…AZD1419 is a TLR9 agonist developed by Dynavax that targets the TLR9 system to modify the immune response in allergic asthma. Another possible therapeutic is to sequester the nucleic acids and this has already been done using a third generation dendrimer that scavengers nucleic acid and this reduced granulation tissue in an animal model [66].…”
Section: Is the Tlr System Druggable?mentioning
confidence: 99%
“…Dendrimers on their own have also been shown to kill multidrug‐resistant pseudomonas strains and can even exert angiogenic effects in wounds 73 . Dendrimers can also serve to scavenge pathogenic molecules, like nucleic acid in pathogenic scarring processes, and decrease wound contraction and augment fibroblast activities 74 . Unlike other NPs, the evidence for the use of growth factor with dendrimers in wounds remains limited, despite favorable results of protein delivery by Dąbkowska et al 75 Additionally, as the structure of dendrimers can easily be changed by drugs, which affects biochemical performance, its clinical potential remains limited to specific drugs combinations that are inert 76 .…”
Section: Nanomaterials and Wound Healingmentioning
confidence: 99%
“…73 Dendrimers can also serve to scavenge pathogenic molecules, like nucleic acid in pathogenic scarring processes, and decrease wound contraction and augment fibroblast activities. 74 Unlike other NPs, the evidence for the use of growth factor with dendrimers in wounds remains limited, despite favorable results of protein delivery by Dąbkowska et al 75 Additionally, as the structure of dendrimers can easily be changed by drugs, which affects biochemical performance, its clinical potential remains limited to specific drugs combinations that are inert. 76 Nevertheless, NPs continue to show potential in improving many aspects of wound healing and will likely remain a topic of interest.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Other irregular immune pathogenesis could also be overcome by the polycations, including systemic lupus erythematosus caused by binding of extracellular DNA and anti-DNA antibodies [89,90]. A recent report showed that topical administration of G3 PAMAM dendrimers could efficiently sequester nucleic acids that cause increase in fibroblast activation and granulation tissue contraction, resulting in decreased pathological scarring during wound healing [91]. In addition, the application of polycations as antithrombotic agents that rapidly remove prothrombotic nucleic acids together with other polyphosphates was also demonstrated in vivo and proposed as a novel strategy to prevent thrombosis after injury [92].…”
Section: Polymeric Sequestrantsmentioning
confidence: 99%